1997
DOI: 10.1097/00004872-199715120-00067
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine-induced vasodilatation in the human hypertensive kidney

Abstract: Administration of ACh to the human hypertensive kidney induces a dose-dependent increase in renal blood flow. This effect is, at least partially, mediated by muscarinic receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…[50][51][52][53] In addition, the activation of muscarinic receptors by acetylcholine induces vasodilatation and increases renal blood flow. [54] Therefore, muscarinic acetylcholine receptors seem to perform an important role in triggering the renal effects of MG, as the pretreatment with atropine completely prevented its diuretic and saluretic effects. On the other hand, while indomethacin was entirely inert to the effects of MG, L-NAME was able to amplify its diuretic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[50][51][52][53] In addition, the activation of muscarinic receptors by acetylcholine induces vasodilatation and increases renal blood flow. [54] Therefore, muscarinic acetylcholine receptors seem to perform an important role in triggering the renal effects of MG, as the pretreatment with atropine completely prevented its diuretic and saluretic effects. On the other hand, while indomethacin was entirely inert to the effects of MG, L-NAME was able to amplify its diuretic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The major vasodilatory agents studied include the prostanoids produced by cyclooxygenase enzyme and nitric oxide released by the different isoforms of the enzyme nitric oxide synthase . In addition, the activation of muscarinic receptors by acetylcholine induces vasodilatation and increases renal blood flow . Therefore, muscarinic acetylcholine receptors seem to perform an important role in triggering the renal effects of MG, as the pretreatment with atropine completely prevented its diuretic and saluretic effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, in earlier studies we showed that both acetylcholine and adenosine induce renal vasodilatation, and that this was adequately detected with our method. 19,20 So, if there was any (net) effect of BNP, it must have been very small. Another limitation of the present study is that for ethical reasons, we could not study healthy subjects.…”
Section: Limitationsmentioning
confidence: 99%
“…Among these, papaverine dilates the renal microcirculation and is more likely to achieve a substantial decrease in RVR and RFR than conduit vessel dilators. However, acetylcholine, 3,5,6,12,13,[47][48][49] the prototypical endothelium-dependent vasodilator of the microcirculation, appears to be associated with greater RFR attended by a smaller and more transient decrease in MAP.…”
Section: Choice Of Vasoactive Substancementioning
confidence: 99%
“…Among these, papaverine dilates the renal microcirculation and is more likely to achieve a substantial decrease in RVR and RFR than conduit vessel dilators. However, acetylcholine, 3,5,6,12,13,[47][48][49] the prototypical endothelium-dependent vasodilator of the microcirculation, appears to be associated with greater RFR attended by a smaller and more transient decrease in MAP.Indeed, using EBCT, we have observed that systemic administration of acetylcholine effectively increased RBF (Figure, part a) accompanied by only a transient decrease in MAP, whereas the dose of sodium nitroprusside required to increase RBF was accompanied by a small but sustained decrease in MAP. 37,40 Intrarenal bolus injections of acetylcholine also dose dependently increased RBF (measured using intravascular Doppler) more effectively than papaverine, in association with smaller decrements in MAP (Figure, part b), suggesting that acetylcholine may be a suitable challenge for RFR.…”
mentioning
confidence: 99%